Addition of dipeptidyl peptidase‐4 inhibitors to insulin treatment in type 2 diabetes patients: A meta‐analysis. Issue 4 (5th December 2017) - Yang, Wenjia; Cai, Xiaoling; Gao, Xueying; Chen, Yifei; Chen, Ling; Ji, Linong
Abstract : The aim of this meta‐analysis is to evaluate the efficacy and safety of combining insulin therapy with dipeptidyl peptidase 4 (DPP‐4) inhibitors compared to combining insulin therapy with placebo or other antihyperglycaemic agents. We found that treatment with DPP‐4 inhibitors combined with insulin improved glycaemic control without an increased risk of hypoglycaemia or weight gain compared with insulin treatment alone. Abstract: Aims/Introduction: To evaluate the efficacy and safety of combining insulin therapy with dipeptidyl peptidase‐4 (DPP‐4) inhibitors compared with combining insulin therapy with a placebo or other antihyperglycemic agents. Materials and Methods: A literature search was carried out via electronic databases. The inclusion criteria were randomized controlled trials comparing the addition of DPP‐4 inhibitors to insulin with the addition of a placebo or other active hypoglycemic agents to insulin therapy, study duration of no less than 12 weeks carried out in type 2 diabetes patients and the availability of outcome data to evaluate a change in the glycated hemoglobin. Results: The glycated hemoglobin‐lowering efficacy was significantly greater with DPP‐4 inhibitor/insulin (DPP‐4i/INS) than with placebo/insulin (weighted mean difference −0.53%, 95% confidence interval −0.63, −0.43, P < 0.01). The postprandial plasma glucose‐lowering efficacies was also significantly greater with DPP‐4i/INS than with placebo/insulin (weighted mean difference −1.65 mmol/L, 95% CI: −2.34, −0.96, P < 0.05). The risk of hypoglycemia or severe hypoglycemia was similar for DPP4i/INS and placebo/insulin treatments. There was no significant difference in the glycemia‐lowering efficacy between DPP‐4i/INS and alpha‐glucosidase inhibitors/insulin, thiazolidinedione/insulin and glucagon‐like peptide‐1 receptor agonist/insulin. Sodium–glucose cotransporter 2 inhibitor/insulin treatment achieved better placebo‐corrected efficacy in lowering postprandial plasma glucose, with less weight gain and no higher risk of hypoglycemia. Conclusions: Treatment with DPP‐4 inhibitors combined with insulin improved glycemic control without an increased risk of hypoglycemia or weight gain compared with insulin treatment alone.